The Responsibility of Banks in the Case of Online Financial Fraud - Khanpruksa, Suwalak (Mae Fah Luang University Law Journal, 2025)
This article aims to study the responsibility of banks in cases of fraud involving online financial transactions. The legal issues arise from cybercrime that has caused significant financial detriment to Thailand. The nature of these crimes is directly related to financial losses for which banks may be held responsible. The study discovers that financial threats can be categorized into two types. The first type is “Unauthorized Payment Fraud,” in which transactions are carried out by impersonating the financial service provider. The second type is “Authorized Payment Fraud,” in which the financial service user is deceived into willingly conducting the transaction themselves. For the first type of financial threat, court rulings indicate a distinction in the “liability of banks” between two scenarios involving unauthorized withdrawals by fraudsters through mobile applications. In cases of unauthorized withdrawals from a “deposit account application,” both the account holder and the bank are held jointly liable, each responsible for half of the damages. In cases of unauthorized withdrawals from a “credit card application,” the bank alone is fully liable and must bear the entire loss. As for the second type of financial threat, there are currently no relevant court precedents that address the issue of the bank’s liability. However, the government has enacted the Emergency Decree on Measures for the Prevention and Suppression of Technological Crimes B.E. 2566 (2023) as an urgent response to address the issue. The Emergency Decree intends to protect innocent citizens who are deceived by losing their assets through mobile phones or electronic means. In the most recent amendment to the Emergency Decree in 2025, a new principle has been established, requiring financial institutions to share responsibility for damage resulting from technology-related crimes.